Superiority of denosumab over bisphosphonates in preventing and treating glucocorticoid-induced osteoporosis: a systematic review and meta-analysis with GRADE quality assessment - Chen, Chiao-Ling; Wang, Jian-Ying (Frontiers in Endocrinology, 2024)
BackgroundThe increasing prevalence of glucocorticoid-induced osteoporosis (GIOP) due to long-term glucocorticoid therapy underscores the need for effective treatment options. Denosumab and bisphosphonates, both key in managing GIOP, require further comparative evaluation to determine their relative efficacy and safety profiles.MethodsWe conducted a systematic review and meta-analysis, adhering to PRISMA guidelines. Our analysis included randomized controlled trials (RCTs) comparing denosumab with bisphosphonates in GIOP management. The outcomes were percent changes in bone mineral density (BMD) at various sites, bone turnovers markers (BTMs) and the incidence of adverse events.ResultsOur study comprised five RCTs with 1,043 participants. The results showed a significant mean difference in BMD percentage change from baseline at LS of 2.87% (95% CI: 1.86 to 3.87, p<0.001) and at TH of 1.39% (95% CI: 0.15 to 2.64, p=0.03). Additionally, the safety profile of denosumab was found to be comparable to bisphosphonates, with no significant increase in the incidence of adverse events or serious adverse reactions.ConclusionsDenosumab proved more effective in enhancing BMD than bisphosphonates in GIOP, maintaining a comparable safety profile. However, the study’s limitations, including heterogeneity and the need for longer-term research, were noted.